Structure–function association of the cerebellar motor network is altered in isolated cervical dystonia - Grimm, Kai; Braaß, Hanna; Sadeghi, Fatemeh; Gelderblom, Mathias; Schulz, Robert; Zittel, Simone (Journal of neurology, 2025)
Background Cervical dystonia (CD) has been recognized as a disorder of the brain’s sensorimotor network. Within this malfunctioning network, the cerebellum plays an important role that needs to be further characterized. Methods To investigate the structural connectivity of the dentato-rubro-thalamic tract (DRTT), probabilistic tractography was performed in 18 CD patients and 18 matched healthy control (HC) subjects. Connectivity was quantified with fractional anisotropy (FA). Thirteen subjects in each group also participated in a neurophysiological double-blind experiment to investigate the effect of cathodal and sham cerebellar transcranial direct current stimulation (ctDCS) on sensorimotor associative plasticity, as evoked by paired associative stimulation (PAS). The association of FA of the DRTT and neurophysiological parameters was studied with linear models. Results The FA of the DRTT was not different between the groups and not related to motor symptom severity in CD patients. In the HC group, there was a significant association between the structural connectivity of the DRTT and the effect that cathodal ctDCS had on the PAS effect. This association was not found in CD patients. Conclusions The microstructural state of the DRTT is a potential biomarker for the efficacy of ctDCS in HC. The lack of this structure–function association in patients is further evidence of abnormal properties of the cerebellar motor network in CD.